Citizen journalism and election monitoring in Nigeria - Tsegyu, Santas (Penerbit Universiti Kebangsaan Malaysia, 2016)
Citizen journalism is fast becoming an alternative platform for the common man to lend their voices in the process of governance. This is especially relevant in Nigeria, where those in the corridor of power have gagged the media denying the citizens the right to contribute to personal or national discourse. Drawing lessons from Nigeria’s Machiavellian leadership recruitment system with attendant prebendal skews in elections characterized by all sorts of irregularities and fraud, the study looks at the role of citizen journalists in monitoring election via social media platform. Survey research method was used for the study, and the questionnaire as instrument for data collection. The respondent for the study comprised of 300 and 400 level students of Mass Communication Department Ibrahim Badamasi Babangida University Lapai. The study purposively sampled 150 respondents for the study. Findings reveal that citizen journalism has a critical role to play in election monitoring in Nigeria. The study discovered that citizen journalism can enhance transparency and accountability in the conduct of elections. This to some extent can bring credibility to the electoral process as citizens would be allowed to participate fully in the electoral process. However, the study noted some inherent dangers associated with citizen journalism / journalists in general. Some of the drawbacks of citizen journalism include the following; it may lead to mass revolt and protest, invasion of people’s privacy, and the dissemination of unverifiable information by members of the public. The study, among other things, recommends that citizen journalists need to be trained in order to be acquainted with the journalistic code of media ethics.